Treatment of murine cryptococcal meningitis with an SCH 39304-amphotericin B combination. - Albert, M M (1991)
Cryptococcal meningitis was induced in BALB/c mice by intracerebral infection with Cryptococcus neoformans. Drug therapy was initiated 1 day later, with mice receiving amphotericin B (AMB), SCH 39304, combination therapy, or no drug therapy (controls). Most, but not all, combinations showed additive benefits, significantly prolonging survival and reducing organism counts in tissues compared with those in controls and groups which received the drugs independently. Optimum protection was obtained when a single dose of 10 mg of AMB per kg of body weight was combined with a fairly narrow SCH 39304 dose range. AMB antagonism did not occur with any regimen tested. AMB-azole combinations may be reasonable alternatives for patients who fail standard cryptococcosis therapeutic regimens.